Fremdsprachenforschung als interdisziplinäres Projekt - Rossa, Henning; Wilden, Eva (Peter Lang International Academic Publishers, 2019)
This book is dedicated to interdisciplinarity, which is characteristic of the approaches, formats and methods of foreign language didactic research. Qualitative and quantitative research approaches or mixed-methods designs are presented on the basis of current studies. A special focus is on the interdisciplinary aspects of the respective studies. The practical research examples present current or near-completion studies in empirical foreign language research. Thus, the contributions provide an up-to-date overview of foreign-language didactic research practice and contain many suggestions for research-methodological options and ethical questions, which must be weighed against newly designed studies in the interdisciplinary field of foreign language research.
Description based on print version record.
KU OGeSoMo
Keywords: Foreign Language Study; Foreign language study; Electronic books